P400 Evolution of clinical and pharmacological parameters after switching from intra-venous to subcutaneous infliximab in patients with inflammatory bowel disease: the REMSWITCH study. (21st January 2022) - Buisson, A; Nachury, M; Reymond, M; Yzet, C; Wils, P; Payen, L; Manlay, L; Pereira, B; Fumery, M
Abstract: Background: Owing to similar efficacy, switching from intravenous (IV) to subcutaneous (SC) infliximab (IFX) is an attractive option, but the feasibility of switching patients with intensified IFX therapy remains unknown. We assessed the clinical and pharmacological evolution after switching from IV to SC IFX in IBD patients to evaluate the feasibility and to determine the equivalence between IV and SC doses. Methods: All IBD patients in clinical remission (CDAI <, 150 or partial Mayo score ≤, 2) were consecutively included in, 3 IBD centers and were switched to SC IFX, 120mg/2 weeks (wk) (regardless of IV dose) at the theoretical day of IV infusion (visit, 0 = V0) and were followed every, 4 to, 8 weeks according to the initial IV regimen for, 6 months. Results: Among, 246 screened patients, 65 (26.4%) were not eligible (no clinical remission or physician's decision), and, 71.8% (130/181) accepted to switch to SC IFX (Crohn's disease = 73, 1%, concomitant immunosuppressant = 25.4%, median faecal calprotectin = 35 µg/g [16–104])., 43.1% of the, 130 patients received, 5mg/kg/8 wk. In, 130 patients, clinical relapse leading to therapeutic escalation was observed in, 11.1% including, 4.0%, 8.6%, 11.1% and, 40.0% in patients treated with, 5mg/kg/8wk, 10 mg/kg/8wk, 10mg/kg/6 wk and, 10mg/kg/4 wk, respectively. Dose increase (240 mg/2 wk) induced clinical remission in, 92.3% of relapsers. Infliximab trough levels (TL) were significantly higher after switching from IV to SC IFX:, 9.8 ±6.4 vs, 14.4 ±5.7 (p<0.0001). TL increased in patients receiving, 5 mg/kg/8 wk (6.3 ±, 3.4 vs, 14.7 ±5.7; p<0.0001) or, 10 mg/kg/8 wk (8.4 ±5.6 vs, 13.7 ±6.6; p=0.001) but remained stable in those treated with, 10 mg/kg/6 wk (11.1 ±7.6 vs, 13.1 ±5.1; p=0.31) or, 10 mg/kg/4 wk (17.8 ±4.2 vs, 15.8 ±4.6; p=0.12) (Figure, 1 ). Infliximab TL remained stable (variation V1-V0 < ±, 1) in, 4.3%, 15.0 %, 33.3 % and, 50.0 % of the patients with the following IV doses:, 5 mg/kg/8 wk, 10 mg/kg/8 wk, 10 mg/kg/6 wk and, 10 mg/kg/4 wk, respectively (p=0.003). No patient developed anti-IFX antibodies. TL before the switch (8.4 ±5.6 for non-relapsers vs, 12.0 ±7.2 for relapsers; p=0.12) and TL after the switch (14.5 ±5.6 vs, 13.6 ±5.6; p=0.63) were not significantly associated with the risk of relapse. In contrast, the risk of relapse was higher in patients with stable or decreasing TL after the switch compared to those with increased TL (31.8% vs, 7.1%; p=0.024). The type of IBD and concomitant immunosuppressant were not associated with the risk of relapse. Patients' acceptability was better with SC injections compared to IV infusions (10pts-acceptability numerical scale = 8.7 ±1.6 vs, 6.8 ±0.9; p<0.0001). Conclusion: Switching from IV to SC IFX is feasible and well-accepted leading to a low risk of relapse in patients with IBD.